Strategi Komunikasi Pemasaran Pariwisata Di Era Digital (Studi Kasus Desa Wisata Kubu Gadang Di Padang Panjang) - Gilang Surendra (Politeknik Negeri Padang, 2023)
Changes in the development paradigm in the era of democratization and regional autonomy, namely from centralized to participatory, provide more open opportunities for community involvement in tourism at the local level. One form of community involvement in tourism is through the establishment of a tourist village. One of the tourist villages in the city of Padang Panjang is the Kubu Gadang Tourist Village. With the increasing number of tourist villages in Indonesia and West Sumatra, tourist villages have to make efforts to plan marketing communication strategies so that they can attract more visitors. Furthermore, to increase tourist visits, the Kubu Gadang Tourist Village has implemented several marketing strategies. This study aims to describe the marketing communication strategy used by Kubu Gadang Tourist Village in today’s digital era. The method used is in this study is descriptive qualitative. The data obtained in this study is from observations and interviews. The results of this study indicate that Kubu Gadang Tourist Village uses a marketing strategy in the form of using digital media such as online media and collaborating with national and local governments.